1988
DOI: 10.1037/0022-3514.54.6.925
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent automatic processing in depression: Accessibility of negative constructs with regard to self but not others.

Abstract: We are grateful to Gordon Logan, Tory Higgins, and two anonymous reviewers for their extensive and valuable comments on an earlier version of this article. We also extend our appreciation to Concepcion Jusino, Jr., and Cathy LaFata for serving as the experimenters for the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
209
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(216 citation statements)
references
References 60 publications
7
209
0
Order By: Relevance
“…In other words, when adolescents try to conceal their identity and suppress their dominant self-concept, the dominant self-concept and its related thoughts may be in the state of deep activation. To examine this potential deep activation state of self-concept and related thoughts, we used a modified Stroop (1935) color-naming task (Mathews & Macleod, 1985) with imposed cognitive load, which has been widely adopted in previous studies on thought suppression, to assess the implicit activation of participants' self-concept by measuring the extent to which self-representation-related words influence performance on cognitive tasks (e.g., Bargh & Tota, 1988;Wegner & Erber, 1992).…”
Section: Accessibility Of Self-representationmentioning
confidence: 99%
“…In other words, when adolescents try to conceal their identity and suppress their dominant self-concept, the dominant self-concept and its related thoughts may be in the state of deep activation. To examine this potential deep activation state of self-concept and related thoughts, we used a modified Stroop (1935) color-naming task (Mathews & Macleod, 1985) with imposed cognitive load, which has been widely adopted in previous studies on thought suppression, to assess the implicit activation of participants' self-concept by measuring the extent to which self-representation-related words influence performance on cognitive tasks (e.g., Bargh & Tota, 1988;Wegner & Erber, 1992).…”
Section: Accessibility Of Self-representationmentioning
confidence: 99%
“…More specifically, studies of social judgment (e.g., Bargh & Tota, 1988) have indicated that frequently activated self-schemata can become chronically accessible over time. Frequently thinking about the self--a defining characteristic of high private self-consciousness--would correspond to frequently activating information about the self.…”
Section: Discussionmentioning
confidence: 99%
“…Prevailing theories have suggested that the self-concept may be understood as part of an associative, propositional network of nodes that resemble words (Bower & Gilligan, 1979;Markus, 1977;Bargh & Tota, 1988;Greenwald et al, 2002;Greenwald & Banaji, 1989;Greenwald & Pratkanis, 1984;Bower & Gilligan, 1979;Kihlstrom & Cantor, 1984). The self is conceived as a node in the network, with activation spreading to and from it.…”
Section: The Embodied Self-conceptmentioning
confidence: 99%